Violações por violência de direitos fundamentais de crianças e adolescentes - Leticia Gramazio Soares; Laís Bastos Depaoli; Maicon Henrique Lentsck; Larissa Gramazio Soares; Marcela Maria Birolim; Ieda Harumi Higarashi (Universidade Federal do Ceará, 2017)
Objective: to describe the violations of the fundamental rights of children and adolescents through violence. Methods: cross-sectional study of notifications of violations collected from the Information System on Protection to Children and Adolescents. Descriptive and analytical analyses were carried out by means of Chisquare tests for associations. Results: among the notifications, 61.2% were related to family and community living; 18.3% to education, culture, sport and leisure; 11.5% to freedom, respect and dignity; 8.5% to life and health; and 0.5% to professionalization and protection at work. There were 541 notifications making reference to violence, which included: 47.5% of sexual nature; white girls, 6 to 12 years old, and students, as main victims; and family members as the main perpetrators. Gender, age and schooling were associated with sexual violence. Conclusion: the fundamental rights of children and adolescents have been violated in most cases by the occurrence of violence of sexual, psychological, and physical nature, and negligence.